Inclusive Literacy: Overview of the Skill of Writing Development in an Inclusive Classroom - Ahmad, Latif (Richtmann Publishing, 2012)
This study reports on an observational study that dwells on conventional views of literacy that how in the most of ourliteracy class rooms a conventional approach to teaching literacy is dominant, at least to pupils with SLD. Children are beingtaught words and phonics, how to get information from books and other kinds of text, and lessons we observed looked verysimilar to those that can be seen in mainstream classrooms all around the country. There is a greater variation for pupils withprofound learning disabilities, but even so, many lessons look, in essence similar to the prescription for the Literacy Hour.